Penerapan Model Pembelajaran Two Stay Two Stray pada Pembelajaran IPA - Eka Lokaria; Aren Frima; Miftahul Jannah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the completeness of learning outcomes after the application of the Two Stay Two Stray model in science learning in Class V SD Negeri 2 Sungai Baung. The research method used is post-test. The population of all fifth graders of SD Negeri 2 Sungai Baung is 38 students and the sample or research subject of some of the population is 38 students. The data collection technique used a test in the form of an essay. The data analysis technique used the